Ecosan (Ecological Sanitation) Based Agroforestry for Boosting Rural Livelihoods - Quli, S. M. S.; Islam, M. A.; Singh, P. K. (Indian Forester, 2016)
The earlier 'Nirmal Bharat Abhiyan' (NBA) and the recent 'Clean India Mission', for promotion of safe sanitation has been the only driving force for this article, which pertains to synergistic union of ECOSAN (Ecological sanitation) with Agroforestry. Various constraints and limiting factors affecting rural livelihoods have been elaborated to highlight the importance of this issue, which advocates for the use of recycled human excreta (urine and faeces) for optimizing the land resource use efficiency through Agroforestry. The benefits, relevance and intricacies of ECOSAN have been reproduced to sensitize the stakeholders for its adoption in Agroforestry systems. Â Suitable tree-crop combinations have been recommended for the different regions of India. The examples and database of enhancement of farm production through use of nutrient rich Human excreta, recycled by ECOSAN, as manure have been reproduced through comparative studies of human excreta vis-Ã -vis conventional fertilizers. This recommendation for innovative Agro forestry is expected to be an incredible cost-effective option to boost the rural livelihoods of India,which suffer a lot due to multidimensional setbacks. Keeping in view the taboos for use of human excreta, only three categories of Agroforestry Systems have been recommended under: Silvi-pastoral, Horti-pastoral and Silvi-horti-pastoral systems. It is expected that the proposed synergistic integration of Agroforestry with ECOSAN would revolutionize the rural livelihoods beside supholding the dignity of rural populations by ensuring a hygienic and eco friendly sanitation system. The free inputs for Agroforestry would substantially boost rural economy as well by cutting down the expenses of fertilizers.